A statistical analysis of properties of small transients in the solar wind 2007–2009: STEREO and Wind observations. Issue 2 (12th February 2014) - Yu, W.; Farrugia, C. J.; Lugaz, N.; Galvin, A. B.; J. Kilpua, E. K.; Kucharek, H.; Möstl, C.; Leitner, M.; Torbert, R. B.; C. Simunac, K. D.; Luhmann, J. G.; Szabo, A.; et al.
Abstract We present a comprehensive statistical analysis of small solar wind transients (STs) in 2007–2009. Extending work on STs by Kilpua et al. (2009) to a 3 year period, we arrive at the following identification criteria: (i) a duration < 12 h, (ii) a low proton temperature and/or a low proton beta, and (iii) enhanced field strength relative to the 3 year average. In addition, it must have at least one of the following: (a) decreased magnetic field variability, (b) large, coherent rotation of the field vector, (c) low Alfvén Mach number, and (d) Te/Tp higher than the 3 year average. These criteria include magnetic flux ropes. We searched for STs using Wind and STEREO data. We exclude Alfvénic fluctuations. Case studies illustrate features of these configurations. In total, we find 126 examples, ∼81% of which lie in the slow solar wind (≤ 450 km s−1). Many start or end with sharp field and flow gradients/discontinuities. Year 2009 had the largest number of STs. The average ST duration is ∼4.3 h, 75%<6 h. Comparing with interplanetary coronal mass ejections (ICMEs) in the same solar minimum, we find the major difference to be that Tp in STs is not significantly less than the expected Tp. Thus, whereas a low Tp is generally considered a very reliable signature of ICMEs, it is not a robust signature of STs. Finally, since plasma β∼1, force‐free modeling of STs having a magnetic flux rope geometry may be inappropriate.